Studi Komparatif terhadap Undang-Undang No. 52 Tahun 2009 dan Hukum Islam tentang Program Keluarga Berencana di Indonesia - Imam Syafi’i; Muhammad Ihwan (Program Pascasarjana Universitas Ibrahimy, 2022)
Law of the Republic of Indonesia No. 52 of 2009 concerning Population Development and Family Development. The movement for controlling and limiting offspring (tahdid al-Nasl) set by the government had become problematic in Islam. The problem is how the practice of family planning in the Law of the Republic of Indonesia no. 52 of 2009 concerning Population Development and Family Development. Then what was the Islamic view on it concerning Population Development and Family Development? After conducting a data study, data exposure, and discussion through existing research methodologies. Population Development and Family Development was an effort to regulate, birth spacing or temporary pregnancy prevention efforts with the agreement of husband and wife due to certain situations and conditions for the benefit of the family, society, and the state. Based on the principles set out in Islam, the program was considered to follow the limits set out in Islam.